EDUCATION FOR THE FISHERMEN COMMUNITY OF BAGAN DELI VILLAGE ABOUT DIGITAL MARKETING OF FISH PROCESSING BUSINESSES - Nidya Banuari; Ahmad Rivai; Roni Juliansyah; Arsyaf Tampubolon; Debora Tambunan; Dompak Pasaribu (RADJA PUBLIKA, 2023)
This study is aimed at equipping the fishing community in Bagan Deli Village with knowledge regarding digital marketing strategies for fish processing businesses, focused on elevating their economic welfare. As a community fundamentally reliant upon natural resources, the people face additional challenges accessing wider markets. This community service activity comprises theoretical and practical training on marketing fish processing products through digital platforms, such as social media and e-commerce. The method includes preparation, cooperative training, and practical demonstrations. The results suggest an increase in awareness and skill in the area of digital marketing among participants, encouraging interdependence and creativity in the application of technology. This initiative aims for sustainable development through a continuous process of mentoring and monitoring.